Incidence rate and structure of external genital endometriosis in hospital patients - Aleksei M. Gerasimov; Anna I. Malyshkina; Marina V. Kuligina; Angelina K. Krasilnikova; Dmitrii M. Polumiskov; Leila Kh. Abdullaeva; Ekaterina V. Fadeeva; Irina Yu. Dvoinova (IP Berlin A.V., 2021)
Aim. To assess the frequency of genital endometriosis and its various forms based on the analysis of hospitalized morbidity. Materials and methods. Analysis of the medical data base of the gynecological clinic of the Gorodkov Ivanovo Research Institute of Maternity and Childhood for the period 20002019. The unit of observation is a case of endometriosis in a patient who left the gynecological clinic of a 24-hour hospital. The clinical characteristics of the prevalence of genital endometriosis are given based on the analysis of 9.378 surgery protocols for the period 20002019. The stages of spread of the endometrioid process were assessed according to the 1985 R-AFS classification. Results. The total number of patients diagnosed with endometriosis was 17% of the total number of gynecological patients. The proportion of hospitalized with endometriosis in 20002019 increased by 2 times from 4.5 to 9.2%. Over 20 years, the proportion of patients with endometriosis of the uterus (N80.0) from 36.2 to 9.0% (p0.001), with endometriosis of the rectovaginal septum and vagina (N80.4) decreased from 2.6 to 0% (p0.01). The proportion of patients with ovarian endometriosis (N80.1) increased from 12.1 to 34.6% (p0.001), pelvic peritoneal endometriosis (N80.3) from 16.5 to 51.1% (p0.001). The proportion of patients with endometriosis of two or more localizations increased from 1.6 to 40.2% (p0.001). Over the 20-year period, there was a decrease in the average age of patients with endometriosis from 37.80.43 years in 2000 to 36.20.34 years in 2009 and 33.80.29 years in 2019 (p0.001). The range of fluctuations in age characteristics ranged from 13 to 55 years. The overwhelming majority of observations are minor forms (I and II stages of the disease) 57.6%. Retrocervical endometriosis was diagnosed in 20.1%. Endometrioid ovarian cysts were in 11.7% of cases. In most cases, endometriotic lesions were combined with adhesions of the small pelvis. Conclusion. Thus, genital endometriosis is a common gynecological pathology, which is often the reason for hospitalization for surgical intervention in women of different age groups. However in most cases affects in most important period in a womans life reproductive. The given data emphasize the need to study and develop therapeutic measures to improve the system of organizing medical care, to find the most optimal and effective forms of diagnosis, approaches to the treatment and rehabilitation of women with endometrisis, which would significantly reduce the volume of surgical interventions, thus reducing financial costs, including overcoming infertility.